MEMBANGUN BRAND AWARENESS PADA USAHA MIKRO KECIL DAN MENENGAH - Riris Mey Rahayu (Kompetensi (Competence : Journal of Management Studies), 2017)
Brand awareness is one way to measure marketing effectiveness as measured by a customer's ability to recognize and / or remember names, images or other signs associated with a particular brand. Brand awareness becomes one of the most important triggers in a strong brand (another trigger is the relevant differentiation). In the current global era of competition in the business world will also be more stringent. The purpose of this research is to make the company especially Micro Small and Medium Enterprises(SME) can carry out their business life by strengthening the brand to the public mind, so that the product produced by a UMKM (Usaha Mikro Kecil dan Menengah) is still in demand by the society and create an impression for the consumer so that the consumer will remain faithful to the product.